NILAI BUDAYA TATTOO PADA KALANGAN ANAK MUDA KOTA MANADO - Satria, Bara; Matheosz, Jenny Nelly; Mamosey, Welly E. (HOLISTIK, Journal Of Social and Culture, 2018)
In Indonesia which consists of various ethnic groups, there are also cultural tattoos. Cultural heritage are found in two ethnic groups in Indonesia, the Dayak in Kalimantan and Mentawai tribe, the Mentawai Islands of inland. The tattoo is a native culture heritage of ancestors who have been there since antiquity. Tattoos for the tribe considered sacred because if they are in the tattoo means will be considered an adult.In   today tattoo has become a reflection for the existence of the society, especially young people.  This get that tattoo is no longer belonged to the clan of thugs and artists, but has become the property of the whole community who love tattoos . The reality shows that the consumption of a tattoo is dominated by young people, both in rural and in urban areas.   On young people in Manado City own tattoos also started a lot of interest. Tattoo enthusiasts not only exist in men, but women have a lot to dare to make the tattoos on his body.The shifting cultural values that were affected by the progress of the era make tattoos for young children into a lifestyle. These changes are caused by the influence of European culture that viewed it a tattoo art, many public figures also use tattoos. Those who use the tattoo considers it a tattoo style language expressed through media images on body. Keywords: tattoo, yong people, culture value